Leveraging Artificial Intelligence Technology to Drive Product Innovation in Digital Business Development - Risma Haris; Sheila Aulia Anjani; Sherli Triandari; Mitra Trima Dessincer Putri; Murphy Mutie (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2026)
The rapid advancement of Artificial Intelligence (AI) has transformed digital businesses by enabling continuous product innovation to sustain competitiveness. This study aims to analyze the role of AI in driving product innovation and supporting digital business development. A quantitative explanatory approach was employed using a survey research design. Primary data were collected from business practitioners and organizational decision-makers who have implemented digital technologies and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that AI significantly enhances product innovation through predictive analytics, machine learning, and intelligent automation, enabling organizations to better understand customer needs, accelerate product development, and improve service quality. Furthermore, AI contributes to greater operational efficiency, stronger competitive advantages, and the development of more adaptive business models. In conclusion, AI serves as a strategic enabler of product innovation and digital business competitiveness, emphasizing the importance of integrating AI into long-term innovation strategies and digital transformation initiatives to achieve sustainable business growth.